Enhancement of spin-dependent hole delocalization in degenerate asymmetric double quantum wells - Kemerink, Martijn; Koenraad, Paulus M.; Christianen, Peter; Geim, Andrey K.; Maan, Jan C.; Wolter, Joachim H.; Henini, Mohamed (Physical review. B, Condensed matter and materials physics, 1996)
Exact, self-consistently calculated eigenfunctions and eigenvalues of the valence band in degenerate asymmetric double quantum wells are obtained from the full 4×4 Luttinger Hamiltonian for different hole densities. We found the solutions to be extremely sensitive to the charge density. The charge induces an extra asymmetry in the confining potential and leads to a smaller separation of the hole levels in the adjacent wells. This strongly enhances the different leakage of wave functions with opposite magnetic moment, called spin-dependent hole delocalization (SDHD). Furthermore, it is shown that the SDHD of the heavy-hole states can be enhanced by increasing the confinement of the light-hole states through adjustment of the height of the confining barriers. The theoretical results are shown to be in excellent agreement with transport and optical experiments, which are proven to be largely determined by space-charge effects. © 1996 The American Physical Society.